The age of acrimony : how Americans fought to fix their democracy, 1865-1915 - Grinspan, Jon (Bloomsbury Publishing, 2021)
"A raucous history of American democracy at its wildest--and a bold rethinking of the relationship between the people and their politics. Democracy was broken. Or that was what many Americans believed in the decades after the Civil War. Shaken by economic and technological disruption, they sought safety in aggressive, tribal partisanship. The results were the loudest, closest, most violent elections in U.S. history, driven by vibrant campaigns that drew our highest-ever voter turnouts. At the century's end, reformers finally restrained this wild system, trading away participation for civility in the process. The result was a calmer, cleaner democracy, but also a more distant one. Americans' voting rates crashed and never recovered. This is the origin story of the "normal" politics of the 20th century. Only by exploring where that civility and restraint came from can we understand what is happening to our democracy today. The Age of Acrimony charts the rise and fall of 19th-century America's unruly politics through the lives of a remarkable father-daughter dynasty. The radical congressman William "Pig Iron" Kelley and his fiery, Progressive daughter Florence Kelley led lives packed with drama, intimately tied to their nation's politics. Through their friendships and feuds, campaigns and crusades, Will and Florie trace the narrative of a democracy in crisis. In telling the tale of what it cost to cool our republic, historian Jon Grinspan reveals our divisive political system's enduring capacity to heal itself"--